Variable Bias Current in Magnetic Bearings for Energy Optimization - Sahinkaya, M. Necip; Hartavi, Ahu E. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
We introduce an adaptive variable bias current control scheme to minimize the energy consumption of magnetic bearings without altering the dynamic performance. We developed analytical expressions for the optimum bias current settings for both differential and unidirectional modes of operation as a function of the orbit size and the desired bearing stiffness. The orbit size is measured in situ by a recursive Fourier coefficient calculation. The analytical results are presented in normalized variables, and hence can be applied to any size and type of magnetic bearing. Both zero and nonzero static load cases are considered. We show analytically that, under variable bias current operation, the differential mode provides better energy efficiency and stiffness capacity than the unidirectional mode. We present the energy consumption data obtained experimentally on a flexible rotor magnetic bearing rig. The data show that, with the proposed variable bias current approach, a significant energy saving can be obtained without deterioration of dynamic performance